Implementasi Zahir Accounting Versi 5.1 Dalam Pengelolaan Data Keuangan Pada Kemang Grosir Bogor - Elvira Febriliani; Sri Wasiyanti; Lisda Widiastuti (Artikel Ilmiah Sistem Informasi Akuntansi, 2022)
Abstract - The development of information technology in the era of globalization, the use of computerized systems in all fields can benefit from the efficiency of time, energy, and material, one of which is in the accounting field. Kemang Wholesale Bogor is a type of business engaged in trading. Kemang Wholesale Bogor in the process of recording operational activities is still done manually using Microsoft Excel in making financial books for each month, monthly reports are made based on daily records, namely the preparation of potentially inaccurate financial reports and delays in completing reports on time. The method of collecting data at Kemang Wholesale Bogor is through the stages of observation, interviewing sources who know the flow of the company's accounting data processing process and searching for literature related to the case study of Kemang Wholesale Bogor. Utilization of Zahir Accounting Software version 5.1 as a solution in processing accounting data and financial reports. By implementing accounting data on the application, it can minimize data input errors so that accurate and timely financial reporting is obtained in its preparation. Keywords: Accounting, Zahir Accounting, Financial Data